Precipitation processes in Al-Cu-Mg-Sn and Al-Cu-Mg-Sn-Ag. (15th April 2016) - Poon, I.; Marceau, R.K.W.; Xia, J.; Liao, X.Z.; Ringer, S.P.
Abstract: Microalloying trace elements into aluminium alloys have been shown to improve mechanical properties by altering the precipitation process. Here, trace amounts of Sn and (Sn + Ag) have been added to Al-1.1Cu-1.7Mg (at.%) and the effects have been investigated by a combination of hardness testing and transmission electron microscopy (TEM). Hardness testing shows that the addition of Sn increases the hardness throughout the ageing process, and in combination with Ag, further increases the hardness and shortens the time to reach the peak hardness. The increase in hardness via Sn microalloying is attributed to the homogeneous distribution of S phase (Al2 CuMg) precipitates. In the alloy microalloyed with both Sn and Ag, the microstructure is dominated by homogeneously distributed Ω phase (Al2 Cu) precipitates in the peak strengthened condition. Given that neither spherical β-Sn precipitates, nor any other obvious nucleation sites for the Ω phase precipitates were observed using TEM, the mechanism for development of such homogeneous precipitation remains to be determined. Graphical abstract: Highlights: Sn and (Sn + Ag) are microalloyed in Al-2.5Cu-1.5Mg (wt%). Hardness and microstructure are examined after solution treatment and ageing. Adding Sn results in superior hardness and homogenises S phase distribution. Adding (Sn + Ag) reduces time to peak hardness and results in Ω phase precipitation.